Opinion | Leave No One Behind: We Need a Rights-Based Approach to Climate Displacement - Baldi, Stefano; John, Anju Anna (Common Dreams, 2023)
Migration needs to be approached as a form of reparation by countries and businesses that have historically contributed most to the problem we face today.
Keywords: 2023-07 July; Climate Displacement; Migration; Refugees